Share Price Performance of Banking Issuers After Dividend Cum-Date - Rahman, Failur; Yunus, Santi; Paskual, Meity F; Achmad, Nuryana Hapirin Dj; Cicilia, Vera Sri Endah (Dinasti Publisher, 2024)
The primary objective of this analysis is to examine the fluctuations in stock prices post dividend distribution, and to evaluate how dividends affect stock performance over a one-year period following their allocation. Statistical analysis using the Paired Sample T-Test is employed to assess time series data in this study. The sample used consists of seven banking issuers, namely BBCA, BBNI, BBRI, BMRI, BTPN, MEGA, and BNGA. The study findings suggest that there is a slight decrease in the performance of banking stock prices the day following the dividend cumdate, though not enough to be considered significant. However, a noticeable difference in share price performance among banking issuers is evident between three months and a year. This was obtained after conducting a paired sample t-test with a result of 0.032. The contraction of stock price performance at cum date in some companies at a certain time, resulting in stock prices falling within a few days. Some of the decline in stock prices after the cum date occurred only a few days or even less than one month, but there were several companies that experienced a longer decline or tended to experience a negative trend for a long time.